Anaerohalosphaera lusitana gen. nov., sp. nov., and Limihaloglobus sulfuriphilus gen. nov., sp. nov., isolated from solar saltern sediments, and proposal of Anaerohalosphaeraceae fam. nov. within the order Sedimentisphaerales. Issue 2 (5th December 2019) - Pradel, Nathalie; Fardeau, Marie-Laure; Tindall, Brian J.; Spring, Stefan
Abstract : Two strains of anaerobic, coccoid, saccharolytic, Gram-stain-negative bacteria were isolated from samples of anoxic hypersaline sediments of evaporation ponds in Tavira (Portugal) and Mallorca (Spain). Both isolates were moderately halophilic, neutrophilic and had a temperature optimum at 37 °C. The highest 16S rRNA gene sequence identity values were found with members of the genus Sedimentisphaera (84.9–88.2 %) within the order Sedimentisphaerales, class Phycisphaerae . The strain SM-Chi-D1 T could be assigned to the family Sedimentisphaeraceae, while phylogenetic analyses based on 16S rRNA gene sequences and genomic data indicate that strain ST-NAGAB-D1 T is both a member of a novel genus and a novel family. SM-Chi-D1 T could be distinguished from other cultured members of the Sedimentisphaeraceae mainly by the stimulatory effect of sulfur on growth, lack of ethanol production during fermentation and several differences in the cellular fatty acids and polar lipids patterns. Main differential characteristics of ST-NAGAB-D1 T were a polytrichous flagellation, the absence of branched chain fatty acids and presence of large proportions of the unsaturated cellular fatty acids C16 : 1  c 9 and C18 : 1  c 11. On the basis of genomic, chemotaxonomic, biochemical and physiological data, we propose the novel species and genera Anaerohalosphaera lusitana gen. nov., sp. nov., and Limihaloglobus sulfuriphilus gen. nov., sp. nov., represented by the type strains ST-NAGAB-D1 T (=DSM 103484 T =JCM 31926 T =KCTC 15600 T ) and SM-Chi-D1 T (=DSM 100118 T =JCM 31927 T =KCTC 15601 T ), respectively. In addition, we propose the novel family Anaerohalosphaeraceae fam. nov. to accommodate the genus Anaerohalosphaera .